The audit risk associated with fraudulent accounting of listed companies in China: a case study - Lei, Lei (2007)
This dissertation studies the discipline of auditing and fraudulent accounting. The investigation of literature review initially concerns about the basic concepts of auditing and audit risk, and then followed by fraudulent accounting which has direct impact on audit risk. The literature tries to discuss audit risk and fraudulent accounting separately and then presents the relationship between the two.